(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Among many questions still open in the growing academic literature regarding mandatory ESG reporting, one of the most important is whether capital markets react positively when firms issue their very first formal ESG report. In this paper, we present the background of our hypothesis that the issuance of the very first formal ESG compliant financial report leads to positive abnormal returns. Based on the principles of information asymmetry, signaling theory, and the relation of ESG reporting and cost of capital, we argue that firms issuing their first ESG report can benefit from a positive abnormal return due to decreased information asymmetry between the firm and ESG-oriented investors.